Portuguese translation and validation of the questionnaires from the Canadian Physical Literacy Assessment-2: a pilot study - Mendoza-Muñoz, María; Carlos-Vivas, Jorge; Castillo-Paredes, Antonio; Parraca, Jose A.; Raimundo, Armando; Alegrete, Joana; Pastor-Cisneros, Raquel; Gomez-Galan, Rafael (Frontiers in Psychology, 2023)
Background/objective Physical literacy assessment is considered a vital resource to decrease the prevalence of sedentary lifestyles and physical inactivity in children and adolescents worldwide. In Portugal, there is no physical literacy assessment tool for children under 15 years old. The main objective of this study was to carry out a translation and cultural adaptation of the Canadian Physical Literacy Assessment 2 (CAPL-2) into Portuguese, as well as to test its psychometric properties, in children between 8 and 12 years of age. Methods The questionnaires included in the CAPL-2 were translated using the translation-back-translation method and adapted to their context. The test–retest reliability, internal consistency, and confirmatory factor analysis of the CAPL-2 Portuguese version were analyzed in a sample of 69 and 138 students, respectively, from a school in the Alentejo region (Portugal). Results The Portuguese version of the CAPL-2 questionnaires demonstrated high internal consistency (Cronbach’s α: 0.713–0.979) and test–retest reliability ranging from moderate to nearly perfect in the motivation and confidence domain and knowledge and comprehension domain (ICC = 0.549–0.932). The results showed a good fit after adjusting for covariation paths (CMIN/DF = 1.382, p = 0.105, RMSEA = 0.053, CFI = 0.971, TLI = 0.955, NFI = 0.907). Conclusion The CAPL-2 version of the questionnaires, translated and adapted to the Portuguese context, demonstrated validity and reliability, making them suitable for assessing physical literacy in children aged 8–12 years.